La face cachée de l’ancestralité. Masques et affinité chez les Matis d’Amazonie brésilienne - Philippe Erikson (Journal de la Société des Américanistes)
Faces from the past. Masks, ancestors and affines of the Matis (Amazonas, Brazil). This paper shows how Matis masks reveal Western Amazonian conceptions of temporality and generational continuity. After a discussion of the ceremonial aspects of the masquerade and of the ontological characteristics attributed to mariwin spirits, it suggests that the latter represent virtual affines rather than ancestors, despite their intimate links with the group’s deceased forebears and endogenous values. Considerations about the possibility of former preferential ritual relations with the neighboring Katukina-Kanamari are also presented.